The relationship between mobile application usages towards job performance at Perkeso Kuantan / Husna Mansor - Mansor, Husna (Faculty of Business and Management, 2018)
This study is conducted to examine the relationship between usages of mobile applications in administration, travel, and communication with job performance. The objective of the study was: (a) to examine whether the employees used mobile applications to perform their tasks; (b) to study what are the most applications used in their smartphone that relates to their job; (c) to investigate whether mobile application influences the job performance of Perkeso employees. For the purpose of this study, 40 employees from six different units were selected through random sampling technique. To achieve the objectives, data were collected through questionnaires. The data analysis showed that mobile applications for administration, travel, communication has significant differences on the job performance of the Perkeso employees. Overall results reflected that most of the employees agreed that their job performance was improved by using mobile applications to carry out their task in administration, traveling or communicating.